Rising Inequalities in Income and Health in China: Who is left behind? - Steef Baeten; Tom Van Ourti; Eddy Van Doorslaer (Tinbergen Institute, 2012)
During the last decades, China has experienced double-digit economic growth rates and rising inequality. This paper implements a new decomposition on the China Health and Nutrition panel Survey (1991-2006) to examine the extent to which changes in level and distribution of incomes and in income mobility are related to health disparities between rich and poor. We find that health disparities in China relate to rising income inequality and in particular to the adverse health and income experience of older (wo)men, but not to the growth rate of average incomes over the last decades. These findings suggest that replacement incomes and pensions at older ages may be one of the most important policy levers in combating health disparities between rich and poor Chinese.
urn:NBN:nl:ui:15-1765/37312
Keywords: C00; D30; D63; I14; I15; 330; China; income growth; income inequality; income mobility; health inequality; Wirtschaftswachstum; Einkommensverteilung; Soziale Mobilität; Soziale Ungleichheit; China